â€œDescriptive study of effects of Matravirudh Aahar.â€: Array - Jeswani , Aruna (Ayurline: International Journal of Research in Indian Medicine, 2021)
Aahar (Diet) always has to be taken in Proper quantity i.e. matra. Although the definition of matra is different for different persons and we see ill health effects if this matra is not maintained. So to analysis these effects we are going to do study & will do conclusion.